Effect of Maternal Prenatal and Postpartum Vitamin D Supplementation on Offspring Bone Mass in Early Childhood: Follow-Up of a Randomized Controlled Trial. (7th June 2021) - O'Callaghan, Karen; Shaila, Shaila; Fariha, Farzana; Harrington, Jennifer; Mahmud, Abdullah Al; Emdin, Abby; Gernand, Alison; Ahmed, Tahmeed; Abrams, Steven; Moore, Daniel; Roth, Daniel
Abstract: Objectives: Maternal vitamin D status has gained substantial attention as a modifiable contributor to offspring musculoskeletal health, yet there is a paucity of trial-derived data to corroborate effects of prenatal or postpartum vitamin D supplementation on offspring bone mass accrual. Among maternal-infant pairs in Bangladesh, we aimed to examine the hypothesized causal association of early life vitamin D exposure with musculoskeletal health in childhood. Methods: In a double-blind dose-ranging trial of maternal vitamin D3 supplementation (Maternal Vitamin D for Infant Growth Trial), healthy pregnant women (n = 1300) were recruited at 17–24 weeks' gestation and randomly assigned to receive a prenatal; postpartum regimen of 0;0, 4200;0, 16, 800;0, 28, 000;0 or 28, 000;28, 000 IU vitamin D3 /week until 26 weeks postpartum. In a follow-up study of offspring at 4 years of age (n = 642), bone mineral content (BMC) and bone mineral density (BMD) were measured by dual-energy X-ray absorptiometry. Between-group differences were assessed by independent t -tests (28, 000 IU/week prenatally vs placebo) and linear regression (each vitamin D treatment group vs placebo) with bootstrapping (1000 replications). Results: Whole-body (WB), total-body-less-head (TBLH) and head-only BMC were similar in the combined high-dose prenatal and placebo groups (mean difference [95% CI] = 6.81g [−8.70, 22.32], 0.61g [−10.90, 12.13] and 1.71g [−3.54, 6.96], respectively). None of the mean values for WB or TBLH BMC or BMD in each vitamin D group were different from placebo ( P  > 0.05 for all comparisons). Although head BMD was slightly greater in offspring of women assigned to the 28, 000;28, 000 IU regimen compared to placebo (mean difference [95% CI] = 0.024g/cm 2  [0.0009,  0.047],   P  = 0.042), the effect was attenuated and no longer significant upon adjustment for child height, weight, and sex ( P  = 0.11). Conclusions: In a population with high prevalence of vitamin D deficiency, our findings do not support the use of maternal prenatal vitamin D supplementation, with or without postpartum supplementation, for improvement of child BMC or BMD at 4 years of age. Funding Sources: Canadian Institutes for Health Research and the Bill and Melinda Gates Foundation.